Determinant of export performance in Malaysian context / Marziah Osman - Osman, Marziah (Faculty of Business and Management, 2007)
The purposed of this study is to identify the factors that influence, stimulate and barriers available in export activities. This research also hoped to act as a knowledge contribution to this subject area by identifying the benefits of export activities to Malaysian exporters. The secondary data is used and the collected data were processed using the SPSS software and Microsoft Excel. The result suggest that gross domestic product, cumulative FDI and Real Effective Exchange rate in US have positive relationship with export. While inflation rate and Real Effective Exchange rate in Malaysia have negative relationship with export.